The association between chronic musculoskeletal pain and clinical outcome in chronic kidney disease patients: a prospective cohort study. (1st January 2019) - Hsu, Heng-Jung; Wu, I-Wen; Hsu, Kuang-Hung; Sun, Chiao-Yin; Hung, Ming-Jui; Chen, Chun-Yu; Tsai, Chi-Jen; Wu, Mai-Szu; Lee, Chin-Chan
Abstract: Background and objectives : Chronic musculoskeletal (MS) pain is common in chronic kidney disease (CKD) patients. The association of chronic MS pain and CKD progression has not yet been established. Method : We conducted a prospective cohort study to evaluate the association of chronic MS pain and CKD progression of pre-dialysis CKD patients. Result : A total of 53.2% of pre-dialysis CKD patients had chronic MS pain. Patients classified as progression and non-progression had a similar prevalence of chronic MS pain at baseline, and similar baseline use of NSAIDs and Chinese herbal medicines. Univariate Cox analysis indicated that chronic MS pain and baseline NSAID or Chinese herbal medicine use were not significantly associated with progression of CKD. But multivariate Cox regression found chronic MS pain was independently significantly associated with all-cause mortality (HR, 2.912, 95% CI, 1.004–8.444; p  = .049). However, serum levels of hs-CRP were similar between those chronic MS pain patients and without chronic MS pain patients (4.96 ± 9.4 vs. 4.25 ± 13.3 mg/L, p  = .535). Conclusion : The CKD patients with chronic MS pain was independently and significantly associated with all-cause mortality, but not independently and significantly associated with CKD progression and composite endpoints. The inflammatory marker-hs-CRP was similar between CKD patients with and without chronic MS pain.